Lymphoid tissue inducer — a divergent member of the ILC family - Zhong, Chao (Cytokine Growth Factor Rev, 2018)
Innate lymphoid cells (ILCs) that are capable of producing effector cytokines reminiscent of CD4(+) T helper (Th) cells during infections and tissue inflammations have drawn much attention in the immunology field in recent years. Within the ILCs, the lymphoid tissue inducer (LTi) cells that play a critical role in lymphoid organogenesis were identified long before the establishment of the ILC concept. LTi cells, developed and functioning mainly at the fetal stage, and LTi-like cells, presumably generated during the adulthood, are regarded as a subset of type 3 ILCs (ILC3s) because they express the ILC3 lineage-defining transcription factor RORγt, and like other ILC3s, can produce an ILC3 signature cytokine IL-22 and initiate protective immune responses against extracellular bacteria. However, LTi/LTi-like cells have a unique gene expression pattern, and they develop from a progenitor that is distinct from the progenitor of all other ILCs and the progenitor of conventional natural killer (cNK) cells. There are also several other unique features of LTi/LTi-like cells comparing to non-LTi ILC3s. In addition to their classical function in lymphoid organogenesis, LTi/LTi-like cells also have specialized functions in association with the adaptive immune system, which include their effects on T and B cell development, activation and function. In this review, we summarize these specific features of LTi/LTi-like cells and propose that these cells should be considered as a separated innate lymphoid lineage in parallel with other non-LTi ILCs and cNK cells.